2014
DOI: 10.1007/s10995-014-1496-x
|View full text |Cite
|
Sign up to set email alerts
|

Social Support, Family Functioning and Parenting Competence in Adolescent Parents

Abstract: Depression is known to mediate the association between low social support and parenting competence in adult mothers, but this relationship is rarely assessed in adolescent mothers and fathers. The primary aim of this study was to identify the association between social support, family functioning and social capital on parenting competence, including self-efficacy and satisfaction in adolescent mothers and their partners. Secondary aims included identifying potential partner effects (e.g. whether a partner's so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
96
1
13

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(122 citation statements)
references
References 33 publications
12
96
1
13
Order By: Relevance
“…As 89% of the participants in the present study were either married or in de facto relationships, there is a high chance that the social support parents were receiving was from their Microsystem, their partner. Consistent with past findings on social support (Angley, Divney, Magriples & Kershaw, 2015); the significant result here could be attributed to both parents sharing infant caregiving responsibilities, this contributing positively to reducing maternal stress.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…As 89% of the participants in the present study were either married or in de facto relationships, there is a high chance that the social support parents were receiving was from their Microsystem, their partner. Consistent with past findings on social support (Angley, Divney, Magriples & Kershaw, 2015); the significant result here could be attributed to both parents sharing infant caregiving responsibilities, this contributing positively to reducing maternal stress.…”
Section: Discussionsupporting
confidence: 92%
“…Having a partner who is available and actively supports, encourages and appreciates the person caring for the child can significantly improve parental mood and health (Bronfenbrenner, 1989). Stable social support from the Microsystem allows for a strong and supportive environment to be formed where both the main caregiver and the child would benefit (Angley et al, 2015). Therefore, this may result in a reduction of stress levels in the environment, and thus, a child's sleep problems my improve (Kataria et al, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…Within Project MAS, the family social workers were nonjudgmental and compassionate with the mothers. A recent study found that social support from families, friends, and professionals was positively correlated with young mothers' confidence in parenting skills [20]. Perhaps the interactions with family social workers from Project MAS with all adolescent mothers in the study may explain the positive outcomes for both groups.…”
mentioning
confidence: 77%
“…Udsatte unge mødre angives f.eks. at opleve mindre social støtte fra sociale netvaerk, hvilket potentielt øger risikoen for ikke at udvikle tilstraekkelig foraeldrekompetence, ligesom mødrene ofte står alene med foraeldreansvaret (Barr & Simons, 2012;Angley et al, 2015). Ligeledes peges på, at børn født af udsatte unge mødre ofte er udsat for mindre omsorg og mindre sensitiv opdragelse og derfor også er svagere stillet rent udviklingsmaessigt sammenlignet med jaevnaldrende børn, der ikke er født af udsatte unge mødre (Laghi et al, 2013;Vinson & Stevens, 2014).…”
Section: Indledningunclassified